Seismic design of steel moment resisting frames: Modal strength reduction factors including strength deterioration and panel zone effects. (13th September 2017) - Loulelis, Dimitris G.; Papagiannopoulos, George A.; Beskos, Dimitri E.
ABSTRACT: Traditional seismic design of framed structures uses a single constant value for the strength reduction factor. In this work, explicit expressions for different values of strength reduction factors for the first significant modes of steel moment resisting frames including strength deterioration and panel zone effects are developed. These factors are functions of modal periods and damage and are designed for four performance levels in a performance – based seismic design framework. The above factors are obtained through extensive parametric studies involving 20 steel frames and 100 far – field ground motions and following a two steps procedure: First an equivalent linear structure with the same mass and elastic stiffness of the original non – linear one is constructed based on equivalent modal damping ratios, which substitute the non‐linearities; then use of these equivalent modal damping ratios in conjunction with modal damping reduction factors leads to modal strength reduction factors. Using these factors, one can obtain the seismic design base shear of a frame through response spectrum analysis. Thus, a more accurate and rational seismic design method is established. Numerical examples are presented to illustrate the method and demonstrate its advantages against conventional seismic design methods.